Improving Disposition Decision-Making for Pediatric Diabetic Ketoacidosis: A Quality Improvement Study. Issue 2 (March 2020) - Kaushal, Tara; Lord, Katherine; Olsen, Robert; Mehta, Sanjiv; Clark, Stephanie; Laskin, Benjamin; Traynor, Danielle; Taylor, April; Shaw, Kathy N.; Srinivasan, Vijay
Abstract : Introduction: In many centers, children with diabetic ketoacidosis (DKA) receive care either in an endocrinology ward or a pediatric intensive care unit (PICU). We conducted a quality improvement (QI) initiative to reduce potentially avoidable PICU admissions of children with DKA without increasing endocrinology ward-to-PICU transfers. Methods: A survey of providers demonstrated opportunities to increase awareness of institutional criteria for PICU admissions of children with DKA. We created an electronic health record (EHR) dot-phrase, prepopulated with these criteria, and placed a note in the EHR for all patients with DKA as a reference for all providers. An EHR-based data report was created to monitor the disposition of DKA patients and the use of the dot-phrase (process measure). The primary outcome measure was the potentially avoidable PICU admissions for patients with DKA. Endocrinology ward-to-PICU transfers were tracked as a balancing measure to ensure safe disposition. Results: After the implementation of the dot-phrase, use was variable, but averaged 33.4% over 1 year. The percentage of DKA admissions classified as potentially avoidable PICU stays decreased from 4.1% to 0.5%, with a concurrent decrease in the total percentage of PICU admissions for DKA from 19.1% to 8.4%. The percentage of endocrinology ward-to-PICU transfers also declined from 0.8% to 0%. Conclusions: A novel EHR-based intervention increasing awareness and documentation of established pediatric DKA management guidelines can be used to safely reduce PICU admissions for DKA without increasing the rate of endocrinology ward-to-intensive care unit transfers.